Screening of endocrine activity of compounds migrating from plastic baby bottles using a multi-receptor panel of in vitro bioassays. (December 2016) - Simon, Coraline; Onghena, Matthias; Covaci, Adrian; Van Hoeck, Els; Van Loco, Joris; Vandermarken, Tara; Van Langenhove, Kersten; Demaegdt, Heidi; Mertens, Birgit; Vandermeiren, Karin; Scippo, Marie-Louise; Elskens, Marc
Abstract: Endocrine activity of 65 compounds migrating from polycarbonate replacement plastic baby bottles was assessed using in vitro cell based assays (reporter gene assays) involving 7 nuclear receptors, i.e. human steroid hormones receptors (oestrogen, androgen, progesterone and glucocorticoid receptors), human thyroid beta and peroxisome proliferator-activated gamma receptors, and the mouse aryl hydrocarbon receptor. The chemicals were tested at 4 concentrations ranging from 0.001 mM to 1 mM. Only twelve chemicals did not show any activity towards any of the nuclear receptors, while fifty three compounds showed a possible endocrine activity. Most of the agonistic activities were observed towards the oestrogen receptor while the PPARγ was the target for most of the recorded antagonistic activities. Agonistic activities were recorded for several phthalates, benzophenones, aromatic hydrocarbons and phenols, while compounds such as benzaldehydes, ketones and esters of fatty acid showed antagonistic activities. Thirty five chemicals were able of agonistic activities on 1 to 4 receptors and antagonistic activities were recorded for 35 compounds as well, towards 1 to 7 receptors. Sixteen compounds were able of both agonistic and antagonistic activities, but not on the same receptors, except in 2 cases for the oestrogen receptor and 4 cases for the PPARγ. Highlights: Endocrine disrupting activity of 65 compounds migrating from polycarbonate replacement plastic baby bottles was assessed. Most of the agonistic activities were observed towards the human oestrogen receptor (29 compounds). Most of the antagonistic activities were observed towards the PPARγ (20 compounds). Thirty five chemicals were able of agonistic activities on 1 to 4 nuclear receptors. Antagonistic activities were recorded for 35 compounds as well, towards 1 to 7 nuclear receptors.